2022
DOI: 10.1186/s12884-022-04636-9
|View full text |Cite
|
Sign up to set email alerts
|

High hemoglobin level is a risk factor for maternal and fetal outcomes of pregnancy in Chinese women: A retrospective cohort study

Abstract: Background To examine the association of hemoglobin (Hb) levels during gestation with the risk of selected adverse pregnancy outcomes such as preterm birth (PTB), low-birth-weight infants (LBW) and small-for-gestational-age infants (SGA) in Chinese women. Methods This retrospective cohort study was conducted in the Department of Gynecology and Obstetrics at the Union Shenzhen Hospital of the Huazhong University of Science and Technology, using rout… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…The findings from this study diverge from the results of similar studies in South Asia, where IFA supplementation and the timing of its initiation were found to be significantly associated with linear growth [ 13 , 14 ] and neonatal mortality [ 7 , 19 , 20 , 21 ]. This contrast that also highlights the importance of context may be explained by the high prevalence of malaria in SSA.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings from this study diverge from the results of similar studies in South Asia, where IFA supplementation and the timing of its initiation were found to be significantly associated with linear growth [ 13 , 14 ] and neonatal mortality [ 7 , 19 , 20 , 21 ]. This contrast that also highlights the importance of context may be explained by the high prevalence of malaria in SSA.…”
Section: Discussioncontrasting
confidence: 99%
“…Multiple studies have shown a positive association of iron and folic acid (IFA) supplementation during pregnancy with fetal growth [ 6 ] and low birth weight [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. However, very few have analyzed the association with a child’s linear growth beyond birth.…”
Section: Introductionmentioning
confidence: 99%
“…Anemia during pregnancy is considered an adverse condition that can affect the health of the maternal–fetal unit according to the World Health Organization (WHO), generally defined with hemoglobin values <11 g/dL. Several studies have demonstrated that hemoglobin values in pregnant women between 9 g/dL and 13 g/dL are not associated with adverse neonatal outcomes [ 12 , 13 , 14 , 15 ]. This is an important question for populations living at HA since they have normally increased Hb levels [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2016) observed a significant interaction between the MTHFR 677TT genotype and being overweight/obesity on the risk of developing type 2 diabetes, with the attributable proportion due to interaction being 0.40 (95% CI: 0.05–0.76) 14 . Similarly, our previous studies had indicated that pregnant women who were obese, with the CT + TT genotype, were 2.40 times more likely to have GDM, whereas no significant association was observed in those with the CC genotype 31 . In addition, an Italian study demonstrated that participants with the C677T CT or TT genotype had a high body weight, BMI, and other anthropometrics at baseline, and lost less weight in the mutated genotype group after dietary intervention 32 .…”
Section: Discussionmentioning
confidence: 65%